Von Willebrand Disease - Putu Reyhan Irza Dhaneswara, I (Jurnal Syntax Fusion, 2022)
Von Willebrand disease is a hereditary bleeding disorder caused by a deficiency of von Willebrand factor. The prevalence of von Willebrand disease is estimated to range from approximately 1% of the general population to 125 clinically proven cases per million population. The main cause of this disease is a decrease in the level or function of abnormal von Willebrand factor due to a point mutation or large deletion that causes disruption of the structure and synthesis of von Willebrand factor. The most common symptoms include bleeding gums, hematuria, epistaxis, urinary tract bleeding, blood in the stool, easy bruising, and menorrhagia. There are several types of von Willebrand disease (VWF), namely type 1, type 2A, and type 2B which are inherited in an autosomal dominant manner, and type 2N, type 3 is inherited in an autosomal recessive manner. Management of VWD cases is generally carried out by administering drugs, plasma transfusions, and avoiding conditions that can cause involuntary injury or bleeding.